2010
DOI: 10.1210/jc.2010-0135
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Preoperative Glycemic Control, Intraoperative Insulin Sensitivity, and Outcomes after Cardiac Surgery

Abstract: In diabetic patients, HbA(1c) levels predict insulin sensitivity during surgery and possibly outcome. Intraoperative insulin resistance is associated with an increased risk of complications, independent of the patient's diabetic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
185
4
26

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(223 citation statements)
references
References 29 publications
8
185
4
26
Order By: Relevance
“…In addition, diabetic patients with HbA1c > 6.5% had a greater incidence of major complications ( P  = 0.010), and minor infections ( P  = 0.006). Such patients received more blood products, and spent more time in the ICU ( P  = 0.030) and the hospital ( P  < 0.001) than metabolically normal patients 21. These findings are in agreement with the results of other observational studies indicating worse outcomes after cardiac, abdominal and vascular procedures in the presence of increased HbA1c concentrations 32, 33, 34…”
Section: Metabolic Homoeostasissupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, diabetic patients with HbA1c > 6.5% had a greater incidence of major complications ( P  = 0.010), and minor infections ( P  = 0.006). Such patients received more blood products, and spent more time in the ICU ( P  = 0.030) and the hospital ( P  < 0.001) than metabolically normal patients 21. These findings are in agreement with the results of other observational studies indicating worse outcomes after cardiac, abdominal and vascular procedures in the presence of increased HbA1c concentrations 32, 33, 34…”
Section: Metabolic Homoeostasissupporting
confidence: 88%
“…Observations made in 273 diabetic and non‐diabetic patients undergoing open heart surgery demonstrated a significant correlation between the quality of pre‐operative glycaemic control as reflected by HbA1c levels and insulin sensitivity during cardiac surgery ( r  = 0.527, P  < 0.001) 21. In addition, diabetic patients with HbA1c > 6.5% had a greater incidence of major complications ( P  = 0.010), and minor infections ( P  = 0.006).…”
Section: Metabolic Homoeostasismentioning
confidence: 99%
“…Their study results showed that the risk of complications (e.g., serious infections) was proportional to the degree of intraoperative insulin resistance. 15 This finding was independent of several other factors, including the presence of diabetes.…”
Section: Insulin Resistance As a Main Pathogenic Factormentioning
confidence: 75%
“…Elevated levels of hemoglobin A1c, an indicator of glucose control in the preceding three months, were found to be predictive of complications after abdominal and cardiac surgery. [45][46][47][48] In non-cardiac non-vascular patients, preoperative blood glucose levels [ 11.1 mmolÁL -1 were associated with a 2.1-fold higher risk in 30-day all-cause mortality and a four-fold higher risk of 30-day cardiovascular mortality. 49 In a large cohort of 61,536 consecutive elective noncardiac surgery patients, poor preoperative glycemic control was related to adverse in-hospital outcomes and one-year mortality.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…25 In a larger cardiac surgery patient population, intraoperative insulin resistance was associated with clinical outcome. 45 Independent of the patient's diabetic state, for every 20% decrease in insulin sensitivity, the risk of serious complications (mortality, myocardial failure, stroke, dialysis, and infection) more than doubled. 45 These findings support the assumption that, perioperatively, acute alterations in glucose homeostasis, i.e., the ''diabetes of the injury'', predict adverse events better than the presence or absence of diabetes mellitus itself.…”
Section: Insulin Resistancementioning
confidence: 99%